The obstacles faced by the junior lecturers of Syiah Kuala University in achieving the required TOEFL scores - Raihal Fajri; Siti Sarah Fitriani; Usman Kasim (Universitas Syiah Kuala, 2021)
The Test of English as a Foreign Language (TOEFL) is an examination used to evaluate a non-native English speaker’s proficiency in the English language. This study was conducted to investigate the obstacles faced by the junior lecturers of Syiah Kuala University in achieving the required TOEFL scores. This research applied a focused description as a method of collecting the data and was located within qualitative research. The population of this research was 23 junior lecturers of Syiah Kuala University who were participating in a training class at the Language Centre of Syiah Kuala University and are in preparation for further study in either home country or overseas universities. The instrument of data collection is a questionnaire guide with google form that was sent to 23 junior lecturers. The questionnaire was used to find out the obstacles faced by the junior lectures in achieving the required TOEFL scores. The collected were analysed by using compiling the percentage, adopting the formula proposed by Sudjono. The finding shows that junior lecturers faced obstacles in answering listening to long conversations with a percentage of 93.3% and avoiding similar sounds with a percentage of 80%. The specific obstacles in the structure written expression section were the skill in answering coordinate connectors, agreement after certain words, and parallel structure with coordinate conjunctions questions with the percentage 60%. The other obstacles were skills in answering agreement after prepositional phrases and skill in agreement after prepositional phrases questions with the percentage 67.7%. Then, the obstacles faced by them in reading comprehension were in recognizing main ideas and determining meanings of difficult words questions with the percentage of 67.7%. It is suggested that the junior lecturers should improve their English proficiency before they take the TOEFL test.